2020
DOI: 10.1136/postgradmedj-2019-137422
|View full text |Cite
|
Sign up to set email alerts
|

Deficient serum furin predicts risk of abdominal obesity: findings from a prospective cohort of Chinese adults

Abstract: BackgroundAs a key enzyme of natriuretic peptides system playing an integral role in energy homeostasis, furin may be a potential contributor to obesity. However, the association between furin and obesity has been scarcely studied. This study aims to examine the prospective association between serum furin and abdominal obesity.MethodsWaist circumference (WC) was measured twice 4 years apart for a total of 892 Chinese adults free of abdominal obesity at baseline. Abdominal obesity was defined as WC over 85 cm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Still, there have been associations established between dysregulated serum furin levels and the occurrence of metabolic diseases like diabetes, hypertension, obesity and cardiovascular disease. While lower serum furin levels were indicative of abdominal obesity and hypertension, higher furin levels were associated with diabetes and myocardial infarction (Fernandez et al, 2018;He et al, 2019He et al, , 2020Wang Y. K. et al, 2020). We speculate that lowered furin levels indicate the increased internalization of Furin for viral cleavage; however, further work is required to ascertain the role of intracellular and extracellular Furin in the development of COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…Still, there have been associations established between dysregulated serum furin levels and the occurrence of metabolic diseases like diabetes, hypertension, obesity and cardiovascular disease. While lower serum furin levels were indicative of abdominal obesity and hypertension, higher furin levels were associated with diabetes and myocardial infarction (Fernandez et al, 2018;He et al, 2019He et al, , 2020Wang Y. K. et al, 2020). We speculate that lowered furin levels indicate the increased internalization of Furin for viral cleavage; however, further work is required to ascertain the role of intracellular and extracellular Furin in the development of COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…A population of 892 Chinese adults without abdominal obesity at baseline was followed-up for four years. They found baseline serum furin deficiency to be a contributor to abdominal obesity [ 146 ]. Gajewska et al determined the iron status in a group of 80 children and found the obese ones to have a 40% increase in hepcidin levels, as well as a 30% reduction in FPN1 levels.…”
Section: Iron Metabolism In Obesitymentioning
confidence: 99%
“…Plasma Furin levels were associated with future DM (Diabetes Mellitus) and obesity, independently of all traditional DM risk factors. Regarding potential mechanisms, as Furin is responsible for the maturation of the insulin pro-receptor; one could speculate that more Furin in the circulation reflects a compensatory mechanism to increase the synthesis of active insulin receptors ( Fernandez et al, 2018 ; He et al, 2020 ). Another possible mechanism of action of Furin in DM development may be via pancreatic beta cells, as Furin has been demonstrated to control the proliferation and differentiation of pancreatic beta cell lines, as well as involvement in the maturation of insulin secretory granules ( Kayo et al, 1997 ).…”
Section: Furin and Covid-19 Infectionmentioning
confidence: 99%